Mental Health Experiences Among Inmates Serving Life Sentences in Ghana Prisons - Baffour, Frank Darkwa (International criminal justice review, 2022)
In Ghana, a convicted person is not entitled to parole. The only hope for their return into the community is either completing the sentence or government amnesty. However, recidivists on life sentences are completely denied the chance of returning into the community. This coupled with the demand of adjusting to the country’s prison conditions affects the mental well-being of life-sentenced inmates. This study explored the mental health experiences of life-sentenced inmates. An interpretive phenomenological approach guided the analysis of qualitative data collected from 21 life-sentenced inmates who were serving terms in three selected prisons. We employed the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) and International Classification of Diseases 11th Revision (ICD-11) mental disorder symptomologies to situate the participants’ narration of their experiences. The participants reported feeling sad, hopelessness, and having sleepless days and nights due to thinking about their perceived spoiled plight. They also experienced stress and were fearful of uncertainties due to perceived prison officer apathy and harsh prison conditions. Additionally, the participants resorted to drug use as a means to cope with their mental health experiences. The participants’ descriptions of their experiences were consistent with some symptomologies of mental disorders as provided in the DSM-5 and ICD-11 and call for the creation of mental health treatment services in the country’s prisons to improve the mental health of inmates.